Pulmonary function predicts mortality and hospitalizations in outpatients with heart failure and preserved ejection fraction. (January 2018) - Andrea, Rut; López-Giraldo, Alejandra; Falces, Carlos; López, Teresa; Sanchis, Laura; Gistau, Concepción; Sabaté, Manel; Sitges, Marta; Brugada, Josep; Agustí, Àlvar
Abstract: Background: Heart failure with preserved ejection fraction (HFPEF) is the most frequent form of heart failure in ambulatory patients with new-onset symptoms. We previously showed that lung function abnormalities are highly prevalent in HFPEF patients. In this observational, longitudinal study, we tested the hypothesis that the presence of airflow limitation and/or arterial hypoxemia predicts mortality and/or cardiovascular hospitalizations during follow-up in HFPEF outpatients. Materials and methods: HFPEF was diagnosed following the international recommendations. Forced spirometry and arterial blood gases were measured at recruitment according to international recommendations. The primary endpoint of the study was all-cause mortality and the secondary one was any cardiovascular hospitalization. Results: We included in the analysis all consecutive outpatients newly diagnosed of HFPEF in our clinic between April 2009 and January 2013 (n = 71). Patients were prospectively followed up for a mean of 4 years (range 10 months to 5.8 years). All-cause mortality was 18.3%. It was higher in patients with airflow limitation (30%) than those with normal spirometry (10%) or other spirometric defects (19%) (p = 0.036). The presence of arterial hypoxemia did not predict mortality (p = 0.179) but was significantly related to cardiovascular hospitalizations during follow-up (p = 0.038). Conclusions: The presence of airflow limitation or arterial hypoxemia identify a group of patients with HFPEF at higher risk of death or cardiovascular hospitalizations, respectively. Given that both airflow limitation and arterial hypoxemia are treatable, we propose that lung function should be routinely evaluated in the outpatient management of HFPEF patients. Highlights: Heart failure with preserved ejection fraction (HFPEF) is prevalent. HFPEF has a poor prognosis. Airflow limitation in outpatients with new-onset HFPEF predicts mortality. Hypoxemia trends to be related to cardiovascular hospitalizations. Lung function evaluation is essential in ambulatory patients with new-onset HFPEF.